Radial basis function circuits using folded cascode differential pairs - Lucks, Marcio B.; Oki, Nobuo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
In this paper, we propose new circuits for the implementation of Radial Basis Functions (RBF). These RBFs are obtained by the subtraction of two differential pair output currents in a folded cascode configuration. We also propose a multidimensional version based on the unidimensional circuits. SPICE simulation and experimental results indicate good functionality. These circuits are intended to be applied in the implementation of radial basis function networks. Possible applications of these networks include transducer signal conditioning and processing in onboard telemetry systems for aircraft and spacecraft vehicles. © 2010 IEEE.
Keywords: Differential pairs; Folded-cascode; Output current; Radial basis functions; Signal conditioning; SPICE simulations; Telemetry systems; Attitude control; Image segmentation; Networks (circuits); Spacecraft; SPICE; Radial basis function networks